Investigating causal relationship among inflammatory cytokines and oropharyngeal cancer: Mendelian randomization - Sibo Xu; Yiguo Li; Wei Chen; Ke Wang (Discover Oncology)
Abstract Objectives This study aims to use Mendelian randomisation to identify the causal relationship between a spectrum of 41 inflammatory cytokines and the development of oropharyngeal cancer. Methods This study investigated genetic variants that have been associated with oral and oropharyngeal cancer using data from a large GWAS. Inflammatory cytokine data were obtained from 8293 asymptomatic individuals. The study primarily used inverse variance weighted and MR-Egger methods to determine the causal relationship between inflammatory cytokines and cancer incidence, complemented by a series of sensitivity analyses including MR-Egger, simple mode, weighted mode, weighted median and leave-one-out approaches. Results Our study demonstrates that higher levels of interleukin-7 (IL-7) and interleukin-5 (IL-5) slightly increase the odds of oropharyngeal cancer by 0.07% [OR: 1.0007, p = 0.005] and 0.04% [OR: 1.0004, p = 0.015], corresponding to a modest increase. Similarly, increased PDGF-bb and CTACK levels are modestly associated with increased odds of oral and oropharyngeal cancer by 0.22% [OR: 1.0022, p = 0.031] and 0.17% [OR: 1.0017, p = 0.043], respectively. Conclusion This investigation posits that IL-5 and IL-7 may be pertinent factors in the etiology of Oropharyngeal cancer, while PDGF bb and CTACK are likely implicated in the pathogenesis of both oral and oropharyngeal cancers.